Arabic Language Rules as A Foundation for Understanding the Meaning of Law in the Qur'an - M Fikar; Mahyudin Ritonga; Abdul Halim Hanafi; Mursal Mursal (Islamic Studies in the World, 2025)
Background. Understanding the meaning of legal verses in the Qur’an requires a rigorous linguistic approach, as Qur’anic law is articulated through highly nuanced Arabic structures, vocabulary, and rhetorical devices. Many misinterpretations of Islamic legal texts stem from insufficient mastery of Arabic language rules, including morphology, syntax, semantics, and contextual pragmatics. Purpose. This study aims to examine how Arabic language rules function as a foundational framework for accurately interpreting the meaning of law in the Qur’an and for deriving sound legal understanding. Method. The research employs a qualitative library-based methodology, utilizing textual analysis of selected Qur’anic legal verses alongside classical works of Arabic grammar (na?w and ?arf), semantics, and Qur’anic exegesis. Data are analyzed through comparative and contextual analysis to identify the relationship between linguistic rules and legal interpretation. Results. The findings demonstrate that Arabic grammatical structures, semantic precision, and rhetorical patterns play a decisive role in determining legal meaning, scope, and implication within Qur’anic texts. Variations in case endings, verb forms, and syntactic constructions significantly influence legal interpretation and normative conclusions. Conclusion. The study concludes that mastery of Arabic language rules is not supplementary but essential for understanding Qur’anic law, as linguistic competence safeguards legal interpretation from reductionism and textual misreading, thereby ensuring methodological accuracy in Islamic legal studies.